2012
DOI: 10.1002/cne.23113
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral facial nerve axotomy in mice causes sprouting of motor axons into perineuronal central white matter: Time course and molecular characterization

Abstract: Generation of new axonal sprouts plays an important role in neural repair. In the current study, we examined the appearance, composition and effects of gene deletions on intrabrainstem sprouts following peripheral facial nerve axotomy. Axotomy was followed by the appearance of galanin ϩ and calcitonin gene-related peptide (CGRP) ϩ sprouts peaking at day 14, matching both large, neuropeptide ϩ subpopulations of axotomized facial motoneurons, but with CGRP ϩ sprouts considerably rarer. Strong immunoreactivity fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 72 publications
(110 reference statements)
0
5
0
Order By: Relevance
“…Our observation of CD44 expression in the periphery of motor neurons is in agreement with previous studies showing its presence in the plasma membrane of neurons (Jones et al, ). Although the function played by CD44 in motor neurons is not clear, some authors suggest that its presence in regenerative axons may indicate a putative role in regulation of axonal outgrowth (Makwana et al, ). The fact that GFAP‐IL6Tg animals showed less expression of both CD44 and CD49e receptors at the time‐points where the neuronal wrapping and synaptic stripping has been described, lead us to speculate that the increase in neuronal death observed in GFAP‐IL6Tg animals could be due to a deficient attachment of microglia and/or lymphocytes to neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Our observation of CD44 expression in the periphery of motor neurons is in agreement with previous studies showing its presence in the plasma membrane of neurons (Jones et al, ). Although the function played by CD44 in motor neurons is not clear, some authors suggest that its presence in regenerative axons may indicate a putative role in regulation of axonal outgrowth (Makwana et al, ). The fact that GFAP‐IL6Tg animals showed less expression of both CD44 and CD49e receptors at the time‐points where the neuronal wrapping and synaptic stripping has been described, lead us to speculate that the increase in neuronal death observed in GFAP‐IL6Tg animals could be due to a deficient attachment of microglia and/or lymphocytes to neurons.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that immunostaining with the galanin and NPY antibodies in the dorsal horn can be abolished by pre-incubation with the corresponding peptide [26,28]. It has also been reported that neuronal staining with the galanin antibody is absent in the brains of galanin knock-out mice [52]. The nNOS antibody labels a band of 155 kDa in Western blots of rat hypothalamus, and immunostaining is abolished by pre-incubation in nNOS [41].…”
Section: Methodsmentioning
confidence: 99%
“…The parvalbumin antibody was raised against mouse parvalbumin and recognises a single band of 13 kDa in blots of mouse brain homogenates [65]. The galanin antibody detects rat galanin, but not substance P, vasoactive intestinal polypeptide or NPY (manufacturer's specification), and it has been reported that staining with this antibody is absent from the brains of galanin knock-out mice [70]. The mouse monoclonal VGAT antibody (raised against amino acids 75-87 of mouse VGAT) labels a single band of 57 kDa in blots of mouse brain and retina, and immunostaining is blocked by preabsorption with the immunising peptide [71].…”
Section: Characterisation Of Antibodiesmentioning
confidence: 99%